Comparative analysis of mesenchymal stem cell surface marker expression for human dental mesenchymal stem cells. (July 2013) - Park, Joo-Young; Jeon, Ho-Jin; Kim, Tae Yun; Lee, Kyeong-Yeoll; Park, Kyoungsook; Lee, Eui Seok; Choi, Je-Min; Park, Chung-Gyu; Jeon, Soung-Hoo
Aim : Human dental mesenchymal stem cells (hDMSCs) have been isolated from extracted human teeth and proven to have different proliferation and differentiation abilities among the subtypes. Despite increasing interest in the clinical use of hDMSCs, a well-defined specific marker has been absent for these stem cells. In this study, a comparative analysis with known mesenchymal stem cell surface markers such as STRO-1, CD90, CD146, CD34 and TfR (CD71) was performed.Materials & methods : Four subtypes of the hDMSCs were obtained and cultured. The hDMSCs were processed by flow cytometric analysis, fluorescence immunocytostaining for in vitro study and in situ immunohistochemical staining for in vivo study.Results & conclusion : The previously known positive and negative MSC markers, such as STRO-1, CD90, CD146 and CD34 showed comparative expression profiles of hDMSC subtypes. TfR was highly positive in hDMSCs compared with the control cells; therefore, TfR was suggested as a new marker for hDMSCs in this study.